Biomechanical Evaluation of Suture Anchor versus Transosseous Tunnel Patellar Tendon Repair Techniques - Sherman, Seth L.; Black, Brandee; Mooberry, Matthew A.; Freeman, Katie L.; Gulbrandsen, Trevor R.; Milles, Jeffrey L.; Evans, Laura; Flood, David; Pfeiffer, Ferris (The Journal of Knee Surgery, 2019)
The objective of this study is to compare the cyclic loading strength and ultimate failure load in suture anchor repair versus transosseous tunnel repair of patellar tendons using a cadaver model. Twelve cadaveric patella specimens were used (six matched pairs). Dual-energy X-ray absorptiometry (DXA) measurements were performed to ensure equal bone quality among groups. All right knees were assigned to the suture anchor repair group (n = 6), whereas all left knees were assigned to the transosseous bone tunnel group (n = 6). Suture type and repair configuration were equivalent. After the respective procedures were performed, each patella was mounted into a gripping jig. Tensile load was applied at a rate of 1 Hz between magnitudes of 50 and 150 N, 50 and 200 N, 50 and 250 N, and tensile load at a rate of 0.1 mm/s until failure. Failure was defined as a sharp deviation in the linear load versus displacement curve, and failure mode was recorded. DXA measurements demonstrated equivalence of bone quality between the two groups (p > 0.05). During cyclic load testing, there was only a statistically significant difference between the groups with regard to cyclic loading at the 50 to 200 N loading cycle (p = 0.010). There was no statistically significant difference between the groups with regard to ultimate load to failure (p = 0.43). Failure mode within the suture anchor cohort occurred through anchor pullout except for one, which failed through the tendon. All specimens within the transosseous cohort failed through the midsubstance of the tendon except for one, which failed through suture breakage. Suture anchor repair demonstrated a similar biomechanical profile regarding cyclic loading and ultimate load to failure when compared with “gold standard” transosseous tunnel patellar tendon repair with a trend toward less gapping in the suture anchor group. Using suture anchors for repair of the patella tendon has similar biomechanical properties to transpatellar tunnels but may provide other clinical advantages.
Keywords: patella tendon rupture; suture anchor repair; transosseous tunnel repair; cyclic loading strength; biomechanics